Scientometric Study: Trends and Patterns in Global Partnership Research - Prima Naomi; Iqbal Akbar (Universitas Proklamasi 45, 2022)
This paper aims to understand the emerging pattern of significance and correlation of the partnership research topics covering all countries. Our study used the scientometric method to reveal the trends and patterns in partnership research. The database was sourced from the scientific literature databases of the Web of Science (WoS). The study recorded 53,800 scientific papers on the partnership in general between 2000 to 2017. GDP and HDI were used to analyze the raison-d’être of the research on partnerships at the macro level. We examined the top 20 countries with the highest GDP, Research Productivity Indicator (RPI), and HDI. A country with a lower Human Development Index (HDI) and higher RPI tends to think that partnerships are essential in supporting national socio-economic development. This study showed that the resource-based view (RBV) theory was discussed more than the stakeholder theory among the two main partnership theories. Observing the motivation to develop partnerships, innovation-seeking was discussed the most in scientific productions. Innovation is used to enhance financial performance and leverage competitive advantage.